Measurement of Blood Loss During Postpartum Hemorrhage. Issue 1 (March 2016) - Lilley, G.; Burkett-St-Laurent, D.; Precious, E.; Bruynseels, D.; Kaye, A.; Sanders, J.; Alikhan, R.; Collins, P.W.; Hall, J.E.; Collis, R.E.
Abstract : ( Int J Obstet Anesth. 2015;24(1):8–14) Rapid and accurate measurement of blood loss during obstetric hemorrhage aids in early diagnosis and intervention and permits appropriate and timely administration of blood and blood products. Blood loss during postpartum hemorrhage (PPH) is commonly estimated visually in clinical practice, but this method has been demonstrated to be inaccurate, with a 30% to 50% underestimation of blood loss, especially for larger volumes.